PENGEMBANGAN LABORATORIUM VIRTUAL SEBAGAI MEDIA PEMBELAJARAN MATERI HDROLISIS DAN LARUTAN PENYANGGA KIMIA DASAR II PRODI PENDIDIKAN KIMIA - Epinur Epinur; Yusnidar Yusnidar (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
ABSTRACT The concepts of hydrolysis and buffer solutions have abstracts related to pH. This concept plays a role in the processes that occur in our bodies and in everyday life. Learning hydrolysis and solution materials requires experiments or practicum, the implementation of practicum is very dependent on the existence and completeness of the laboratory. With advances in technology in the field of ICT, there are many programs available that can be used to design ICT-based practicums (virtual labs). Virtual laboratory can overcome the limitations of laboratories, tools and materials, time and can save costs.This development research aims to determine the feasibility (theoretical and practical) of the developed virtual laboratory for hydrolysis material and buffer solutions. The virtual laboratory for hydrolysis and buffer solutions was developed using the Adobe Flash6 Professional program.This type of research is development research. The product developed is a virtual laboratory using the Adobe Flash6 Professional program for hydrolysis and Basic Chemistry II buffering materials in chemistry education study programs. This virtual laboratory development research uses the ADDIE model.The results of material validation and virtual laboratory media for hydrolysis and buffer solutions were 91% (very good) and 90% (very good). Student learning outcomes average 79.5 (very good)So it can be concluded that the developed virtual laboratory of hydrolysis material and buffer solutions is theoretically feasible and practical and can improve student learning outcomes. Keywords: Virtual Laboratory, Hydrolysis, Buffer Solution@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:none; text-autospace:none; font-size:11.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0021;}h1 {mso-style-priority:9; mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"Heading 1 Char"; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:29.3pt; margin-bottom:.0001pt; mso-pagination:none; mso-outline-level:1; text-autospace:none; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-font-kerning:0pt; mso-ansi-language:#0021;}p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {mso-style-priority:1; mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"Body Text Char"; margin:0cm; margin-bottom:.0001pt; mso-pagination:none; text-autospace:none; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0021;}span.Heading1Char {mso-style-name:"Heading 1 Char"; mso-style-priority:9; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Heading 1"; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman",serif; mso-ascii-font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-hansi-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:#0021; font-weight:bold;}span.BodyTextChar {mso-style-name:"Body Text Char"; mso-style-priority:1; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Body Text"; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman",serif; mso-ascii-font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-hansi-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:#0021;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:11.0pt; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US;}.MsoPapDefault {mso-style-type:export-only; mso-pagination:none; text-autospace:none;}div.WordSection1 {page:WordSection1;}